Eight things SOA is not what not to do in your next SOA rollout. - O'Connor, Paul
Sometimes when we're faced with addressing a complex engineering problem it's helpful to reflect on antipatterns. Doing so does more than track wrong solutions to common problems; it also focuses the mind on the interaction of the most important elements of the problem domain. This is true for all engineering, not just software engineering. Suspension bridge designers know to be on the lookout for torsional oscillations because of the collapse of the Tacoma Narrows Bridge, but they also better understand the importance of stiffening the structure in general. The goal is to limit the number of times the antipattern emerges and to notice it when it comes around again. SOA uptake is at a point where such a treatment of antipatterns is helpful.